2003
DOI: 10.1002/bem.10078
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic fields prevent osteoporosis in an ovariectomized female rat model: A prostaglandin E2‐associated process

Abstract: With the use of Helmholtz coils and pulsed electromagnetic field (PEMF) stimulators to generate uniform time varying electromagnetic fields, the effects of extremely low frequency electromagnetic fields on osteoporosis and serum prostaglandin E(2) (PGE(2)) concentration were investigated in bilaterally ovariectomized rats. Thirty-five 3 month old female Sprague-Dawley rats were randomly divided into five different groups: intact (INT), ovariectomy (OVX), aspirin treated (ASP), PEMF stimulation (PEMF + OVX), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 36 publications
2
84
0
1
Order By: Relevance
“…MRI device, works with radio frequency (RF) radiation and it causes electromagnetic field radiation. In literature, low frequency electromagnetic wave is used in order to heal bone fractures and to increase bone mineral density (11,12). But in these studies, it has been showed that electromagnetic wave is used in medicine by low frequency and pulse (15-72 Hz) (13).…”
Section: Discussionmentioning
confidence: 99%
“…MRI device, works with radio frequency (RF) radiation and it causes electromagnetic field radiation. In literature, low frequency electromagnetic wave is used in order to heal bone fractures and to increase bone mineral density (11,12). But in these studies, it has been showed that electromagnetic wave is used in medicine by low frequency and pulse (15-72 Hz) (13).…”
Section: Discussionmentioning
confidence: 99%
“…In other experimental studies, EM radiation of 0.4 T for 30 minutes a day for 30 days at 15 MHz and 8 MHz was found to have a beneficial effect on osteoporosis [11]. A regulatory effect of EM radiation (2 hours per day for 9 days) on trabecular bone structure in bilateral oopherectomised rats was found by Chang and Chang [10]. Tsai et al reported stimulation of human mesenchymal stem cells (hMSCs) by rectangular pulse PEMF radiation (7.5 Hz for 2 hours per day for 14 days) [24].…”
Section: Journal Of Clinical and Analytical Medicinementioning
confidence: 74%
“…Our results were perhaps not as good as they could have been, had we exposed the rats to longer periods (more than one hour) of EM radiation per day, or for more days (longer than seven days), or at a lower frequency (less than 900 MHz). We used 900 Mhz because that is a standard transmission frequency of mobile telephones, but it is much higher than the frequencies of EM radiation used in experimental healing research, for example, in the studies by Chang, Zhang and Tsai [10,11,39]. Low frequency electromagnetic radiation may have more therapeutic potential in fracture healing than high frequency EM radiation [11,22,23].…”
Section: Journal Of Clinical and Analytical Medicinementioning
confidence: 99%
See 2 more Smart Citations